Short amplicon reverse transcription-polymerase chain reaction detects aberrant splicing in genes with low expression in blood missed by ribonucleic acid sequencing analysis for clinical diagnosis - Wai, Htoo A; Constable, Matthew; Drewes, Cosima; Davies, Ian C; Svobodova, Eliska; Dempsey, Esther; Saggar, Anand; Homfray, Tessa; Mansour, Sahar; Douzgou, Sofia; Barr, Kate; Mercer, Catherine; et al. (Human mutation, 2022)
Use of blood RNA sequencing (RNA-seq) as a splicing analysis tool for clinical interpretation of variants of uncertain significance (VUSs) found via whole-genome and exome sequencing can be difficult for genes that have low expression in the blood due to insufficient read count coverage aligned to specific genes of interest. Here, we present a short amplicon reverse transcription-polymerase chain reaction(RT-PCR) for the detection of genes with low blood expression. Short amplicon RT-PCR, is designed to span three exons where an exon harboring a variant is flanked by one upstream and one downstream exon. We tested short amplicon RT-PCRs for genes that have median transcripts per million (TPM) values less than one according to the genotype-tissue expression database. Median TPM values of genes analyzed in this study are SYN1 = 0.8549, COL1A1 = 0.6275, TCF4 = 0.4009, DSP = .2894, TTN = 0.2851, COL5A2 = 0.1036, TERT = 0.04452, NTRK2 = 0.0344, ABCA4 = 0.00744, PRPH = 0, and WT1 = 0. All these genes show insufficient exon-spanning read coverage in our RNA-seq data to allow splicing analysis. We successfully detected all genes tested except PRPH and WT1. Aberrant splicing was detected in SYN1, TCF4, NTRK2, TTN, and TERT VUSs. Therefore, our results show short amplicon RT-PCR is a useful alternative for the analysis of splicing events in genes with low TPM in blood RNA for clinical diagnostics.
Keywords: ATP-Binding Cassette Transporters; RT-PCR; VUS; Humans; alternativní sestřih; RNA-seq; lidé; ABC transportéry; Alternative Splicing; aberrant splicing; Reverse Transcriptase Polymerase Chain Reaction; sestřih RNA; RNA Splicing; blood RNA; RNA; Reverse Transcription; polymerázová řetězová reakce s reverzní transkripcí; reverzní transkripce